A no can make space - Linehan, Daniel ([Gent] : MER. Paper Kunsthalle, 2013)
A No Can Make Space is a book as a choreography. For this publication choreographer Daniel Linehan has gathered texts and poetic fragments, which he used as part of his choreographic practice. He organized these writings into several chapters according to their main themes: repetition, sequence, rhythm, value, change, tension, silence. A No Can Make Space is an artistic project of collecting and categorizing, a method Linehan often uses when making dance performances. Thus this book becomes a way to think about how making a book can be an extension of making a dance.
Created in the frame of Daniel Linehan’s residency 2012-2013 as artiste associé at deSingel International Arts Campus
N° 178/240
boek
Keywords: Linehan, Daniel